The role of leadership in HRH development in challenging public health settings - Timmons Barbara K; O'Brien Julie; Schiffbauer Judith; Kiarie William N (BMC, 2008)
Abstract As part of the special feature on leadership and human resources (HR), Management Sciences for Health profiles three leaders who have made a significance difference in the HR situation in their countries. By taking a comprehensive approach and working in partnership with stakeholders, these leaders demonstrate that strengthening health workforce planning, management, and training can have a positive effect on the performance of the health sector. Three profiles are presented, from Afghanistan, South Africa, and Southern Sudan, revealing common approaches and leadership traits while demonstrating the specificity of local contexts.